THE USE OF PREDICTION GUIDE METHOD TO IMPROVE STUDENTS’ ACHIEVEMENT IN MASTERING VOCABULARY - HALIMAH TUSSA’DIAH (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This research aimed to implement Prediction Guide Method to Improve students’ achievement in mastering vocabulary. The subject of this research was the IX grade students of SMP Swasta Dr. Cipto Mangun Kusumo Perdagangan of 2015/2016 Academic Year. It consisted of one class with 32 students as the subject. The objectives was discover the improvement of the students’ achievement in mastering vocabulary by using Prediction Guide Method. This research was conducted by using class room action research. The technique analyzing the data was by qualitative and quantitative. The qualitative data were taken from diary note. The quantitative data were taken from the test which were carried out in two cycles and those two cycles were conducted in six meetings. the test were given to the students in the form of pre-test, post test I in the first cycle, and post test II in the second cycle. The result of data analysis showed that there wan an improvement on the students’ achievement inmastering vocabulary from each cycle. It was showed from the mean of pre-test which was 50,31. after Prediction Guide Method was applied in the first cycle, there was a improvement of the result of the students’ mean which was 64,68, and for the second cycle after reflection on the first cycle, there was an improvement of the students’mean which was 90,00. In other words, the students’achievement inmastering vocabulary was improved and based on dairy note, it showed that the motivation and excitement of the students when studying were also improved.